Multifunctional Patented Nanotherapeutics for Cancer Intervention: 2010- Onwards - Pandey, Parijat; Chopra, Hitesh; Kaushik, Deepak; Verma, Ravinder; Purohit, Deepika; Parashar, Jatin; Mittal, Vineet; Rahman, Md. H.; Bhatia, Saurabh; Kumar, Pradeep; Bhattacharya, Tanima; Tagde, Priti; et al. (Recent Patents on Anti-Cancer Drug Discovery, 2023)
Even today, cancer is one of the prominent leading causes of death worldwide. However, there are a couple of treatment options available for management, but the adverse effects are more prominent as compared to therapeutic effects. Therefore, there is a need to design some midway that may help to bypass the negative effects or lower their severity. Nanotechnology has addressed many issues, still many miles are needed to cover before reaching the center stage. The developed nanoformulations can target distant organs owing to their multifunctionality and targeting potential. Stimuli-responsive nanomedicine is one of the most exploited formulations. They can encapsulate and release the drugs for a higher period. However, they release a burst mechanism. The other nanoformulations contain dendrimers, micelles, and lipid-based nano-formulations that have been developed and evaluated for their efficacy in cancer treatment. This review paper highlights some significant patents granted/applied in various patent offices around the globe to treat cancer using the nanotechnology. The Google Patent, United States Patent and Trademark Office (USPTO), Escapenet, and many others were used as the search engine for patent search, and data were collected and analyzed. They used these patented technologies for diagnostic and treatment options, enhancing the absorption, distribution, metabolism, and excretion (ADME) profile of therapeutic molecules.
Keywords: anti-cancer